2018
DOI: 10.1007/s40509-018-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic shielding of quantum entanglement states

Abstract: The measure of quantum entanglement is determined for any dimer, either ferromagnetic or antiferromagnetic, spin-1/2 Heisenberg systems in the presence of external magnetic field. The physical quantity proposed as a measure of thermal quantum entanglement is the distance between states defined through the Hilbert-Schmidt norm. It has been shown that for ferromagnetic systems there is no entanglement at all. However, although under applied magnetic field, antiferromagnetic spin-1/2 dimers exhibit entanglement f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The interest in quantum entanglement brings the localized spin systems of cluster geometry to the attention of the theoreticians [21][22][23][24]. In such context, a variety of geometries can be mentioned, like dimers [25][26][27][28][29][30][31][32][33][34][35][36], trimers [37][38][39][40][41][42][43] or four-site structures [44][45][46][47][48][49][50][51][52]. Attention is paid to design of cluster structures offering advantageous properties due to interplay between geometry and spin-spin interactions [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in quantum entanglement brings the localized spin systems of cluster geometry to the attention of the theoreticians [21][22][23][24]. In such context, a variety of geometries can be mentioned, like dimers [25][26][27][28][29][30][31][32][33][34][35][36], trimers [37][38][39][40][41][42][43] or four-site structures [44][45][46][47][48][49][50][51][52]. Attention is paid to design of cluster structures offering advantageous properties due to interplay between geometry and spin-spin interactions [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…vacuum [4,3], thermal [5], squeezed [11], coherent • • • ) have been considered as prototypical continuum variables, which is natural because they can be created and assisted via linear optics. Recently, it was shown that the entanglement can be assisted via temperature [5], magnetic field [17] and both in [18], but most of them dealt with time independent potential.…”
Section: Introductionmentioning
confidence: 99%